PEMBERDAYAAN EKONOMI PESANTREN MELALUI OPTIMALISASI PENGELOLAAN SAMPAH DENGAN TEKNOLOGI MESIN PENCACAH ORGANIK DI PONDOK PESANTREN AN-NUR - Wulandari, NoviDiah; Pratiwi, Nurna; Pristisahida, Adelia Octora; Guna, Miqod Adi; Amalia, Lutfi; Suroyyah, Liya; Oktariantara, Ibra; Rohmadi, Imam (Universitas Mataram, 2024)
Pondok Pesantren An-Nur in Bantul, Yogyakarta, was established by K.H. Nawawi Abdul Aziz in 1978 and is a prominent Islamic educational institution that also plays a significant role in community outreach and empowerment. With a large number of students, this pesantren faces challenges in waste management, particularly with organic waste, which reaches up to 3.1 tons per day. This community service project aims to enhance waste management at Pondok Pesantren An-Nur by introducing an organic waste shredder machine to accelerate decomposition and increase maggot production used for decomposition. Through this initiative, it is hoped that there will be improvements in environmental conditions and economic benefits for the pesantren. Additionally, the program will provide practical learning experiences for students and contribute to academic dissemination. The main challenges include the large volume of waste and the need for ongoing education about environmental awareness.